Chromosome-Level Genome Assembly of Callitettix versicolor (Rice Spittlebug). (20th August 2022) - Chen, Hong; Qiao, Gexia; Liang, Aiping
Abstract: The spittlebug family Cercopidae (Hemiptera: Auchenorrhyncha: Cicadomorpha: Cercopoidea) is distributed worldwide. Some Cercopidae species are agricultural pests that are responsible for substantial economic damage. However, the genomics of spittlebugs has rarely been studied and their complete genome assembly is yet to be reported. Here, we present the draft reference genome of Callitettix versicolor Fabricius (Hemiptera: Cercopidae) at the chromosome level. The assembled draft genome was 974.99 Mb with a contig N50 of 5.63 Mb, and the longest contig being 24.54 Mb. Hi-C technology was used to obtain an approximately 958.71 Mb chromosome-level genome on 10 pseudochromosomes, which covered 98.33% of the assembly. Repeat sequences accounted for 38.88% of the genomic sequences. A total of 21, 937 protein-coding genes were detected in the reference genome, 89.97% of which were annotated in public databases. The high-quality reference genome of C. versicolor reported in this study will provide a valuable genomic resource for future ecological and evolutionary studies of spittlebugs.